EVOLUTIONARY TRACKS OF SHORT-PERIODIC METEOR SWARMS - Kramer, E. N.; Shestaka, I. S.; Gorbanev, Yu. M. (Одеські астрономічні публікації, 2017)
The relations of the meteor streams with comets and asteroids are determined by means of the  physical and dynamic properties of these bodies. The mathematical model is considered for the short-periodic meteor stream, the particles of which are ejected from the asteroid 3200 Phaeton with the velocities of about 700 m/s. It is shown, that in this case, the original comparatively compact meteor stream is dispersed gradually under the influence of the secular perturbations. At present, after 20000 years, the streams’ orbits are crossing the ecliptic plane along the nearly closed narrow band, the distribution of their arguments of perihelia turning to the uniform one as well as the sporadic background. Owing to this, the opportunity arises to-observe Simultaneously the very faint meteor showers only at the Earth and other terrestrial planets. The existence of the abundant annual Geminid meteor shower doesn’t agree with the considered model and test the suggestion that the particles of this stream were ejected from the Phaeton either not long ago or at small velocities of about tenths of a meter per second, since the meteor stream ejected only at such velocities remains comparatively compact and highly productive one throughout many thousand years. Since the secular perturbations result in the oscillations of the line of apsides of the stream’s orbits (with the period of about 30-40 thousands of years) and in changes of the argument of the perihelion of about 360, the stream approached the Earth four times during this interval and produced the corresponding showers. It is shown that such showers are occurring in different epochs, not during the same year, as some scientists erroneously supposed.